INTEGRATIVE DIMENSIONS OF REFLEXIVE CAPABILITY AND INTELLECTUAL PERFORMANCE IN MODERN EDUCATIONAL AND PROFESSIONAL DEVELOPMENT (Proceedings of International Conference on Educational Discoveries and Humanities, 2024)
This study investigates how reflective ability integrates with intellectual activity to support student development. Reflection is shown as key to self-awareness, regulation, and intellectual growth, with insights from various cultural perspectives highlighting its role in shaping self-knowledge and behavior.